Model symulacyjny kanalizacji podciśnieniowej w Lubiechowie = Simulation model of vacuum sewer system in Lubiechów - Ogiołda, Ewa; Strycki, Oswald (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of wastewater transport methods applied for a small number of houses in villages is vacuum system. In this paper its rules of operation and calculation of system elements in Lubiechów were shown. Results of calculation and possibilities of simulation model prepared in EPANET advantages were also presented.
Keywords: kanalizacja podciśnieniowa; obliczenia symulacyjne; vacuum sewer system; simulation calculation